Towards Non-Invasive Bedside Monitoring of Cerebral Blood Flow and Oxygen Metabolism in Brain-Injured Patients with Near-Infrared Spectroscopy - Diop, Mamadou; Elliott, Jonathan T.; Lee, Ting-Yim; Lawrence, Keith St. (IntechOpen, 2012)
None